Confirmatory Factor Analysis Job Relevant Information, Partisipasi Anggaran dan Kinerja Aparatur Pemerintah Daerah Kabupaten Malang - M Taufiq Noor Rokhman (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2018)
The purpose of this study was to analyze the confirmatory factors of job relevant information, participation in budgeting and the performance of local government apparatus in the Regional Government of Malang Regency. Analysis of the data used in the study using confirmatory factor analysis (CFA) technique, the results of the study showed that active indicators contributed to the strongest budgeting as a variable forming Budget Participation, the indicator gained the strongest strategy as a variable Job relevant information and indicators set budget targets with the strongest resources and time determined as a variable for apparatus performance